The Effects of Oral Rehmannia glutinosa Polysaccharide Administration on Immune Responses, Antioxidant Activity and Resistance Against Aeromonas hydrophila in the Common Carp, Cyprinus carpio L - Feng, Jun-chang; Cai, Zhong-liang; Zhang, Xuan-pu; Chen, Yong-yan; Chang, Xu-lu; Wang, Xian-feng; Qin, Chao-bin; Yan, Xiao; Ma, Xiao; Zhang, Jian-xin; Nie, Guo-xing (Frontiers in Immunology, 2020)
The effects of the oral administration of Rehmannia glutinosa polysaccharide (RGP-1) on the immunoregulatory properties, antioxidant activity and resistance against Aeromonas hydrophila in Cyprinus carpio L. were investigated. The purified RGP-1 (250, 500 and 1000 μg/mL) was co-cultured with the head kidney cells of the common carp. The proliferation and phagocytosis activities of the head kidney cells, and the concentration of nitric oxide (NO) and cytokines in the culture medium were determined. Next, 300 common carps (47.66 ± 0.43 g) were randomly divided into five groups; the two control groups (negative and positive) were administered sterile PBS and the three treatment groups were administered different concentrations of RGP-1 (250, 500 and 1000 μg/mL) for seven days. Subsequently, the positive and treatment groups were infected with A. hydrophila, and the negative group was administered sterile PBS for 24 h. The concentration of NO, cytokines, lysozyme (LZM) and alkaline phosphatase (AKP) in serum, the total antioxidant capacity (T-AOC), the levels of malonaldehyde (MDA) and glutathione (GSH), and the total activities of superoxide dismutase (T-SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) in the hepatopancreas of the common carp were tested. We observed that RGP-1 could significantly enhance the proliferation and phagocytosis activities (P < 0.05), besides inducing the production of NO, pro-inflammatory cytokines (TNF-α, IL-1β, IL-6, IL-12) and anti-inflammatory cytokines (IL-10, TGF-β) (P < 0.05) in vitro. The in vivo experimental results revealed that RGP-1 significantly enhanced NO production, protein levels of pro-inflammatory cytokines (TNF-α, IL-1β, IL-6, IL-12), LZM and AKP activities, and the antioxidant content (T-AOC, SOD, CAT, GSH, GSH-Px and MDA) compared to that observed in the negative group prior to A. hydrophila infection (P < 0.05). NO, pro-inflammatory cytokines, LZM and AKP activities were significantly lower than that in the positive group after infection (P < 0.05). However, whether infected or not, the expression of anti-inflammatory cytokines (IL-10, TGF-β) increased significantly in the RGP-1-treated groups (P<0.05). Therefore, the results suggested that RGP-1 could enhance the non-specific immunity, antioxidant activity and anti-A. hydrophila activity of the common carp, and could be used as a safe and effective feed additive in aquaculture.